Experimental characterization of an earth eco-efficient plastering mortar - Santos, Tânia (2015)
Earthen plastering mortars are becoming recognized as highly eco-efficient. The assessment of their technical properties needs to be standardized but only the German standard DIN 18947 exists for the moment. An extended experimental campaign was developed in order to assess multiple properties of a ready-mixed earth plastering mortar and also to increase scientific knowledge of the influence of test procedures on those properties. The experimental campaign showed that some aspects related to the equipment, type of samples and sample preparation can be very important, while others seemed to have less influence on the results and the classification of mortars. It also showed that some complementary tests can easily be performed and considered together with the standardized ones, while others may need to be improved. The plaster satisfied the requirements of the existing German standard but, most importantly, it seemed adequate for application as rehabilitation plaster on historic and modern masonry buildings. Apart from their aesthetic aspect, the contribution of earthen plasters to eco-efficiency and particularly to hygrometric indoor comfort should be highlighted.